Polityka socjalna i sytuacja ludzi w podeszłym wieku - Piotr Krajewski (Studia Ecologiae et Bioethicae)
We have observed great interest in the phenomenon of aging of the population and its consequences. On the hand, all who are much younger should learn how to grow old taking into account that the phenomenon of life is a dynamic process and it is not connected with the present day but the future which will come very fast, that is why, it should not find us unprepared.